THEORETICAL BASES OF ECONOMIC MEASUREMENT OF VALUE IN THE CONDITIONS OF GLOBAL TECHNOLOGICAL SHIFTS AND CRISES. NEWEST METHODOLOGICAL BASE (PART 2) - O. E. Medvedeva (Publishing House of the State University of Management, 2020)
The problems of measuring scientific and technical progress in the transition to the sixth technological mode have been considered. Nowadays scientific and technical progress is measured mainly by natural indicators. Forecasting requires a valuation of capital, taking into account fluctuations in the interest rate at the macro level; assessment of public production efficiency and new technologies. The applied methodology for such assessments has not yet been formulated. For these purposes, the methodology of the theory of economic measurements, which is also at the infancy stage and its latest concepts can serve. In relation to scientific and technical progress, the object of assessment may be the cost of capital and its depreciation in the final phase of the transition period, the effectiveness of scientific and technical progress and the money itself, considered as the main measure of value, and creating the effects of procyclical cost of capital in the conditions of technological shifts and crises.